Home Appliances SMS Controller - Zarif , Che Hashim (UTeM, 2010)
This project focuses on how to control electrical switch for house appliances(eg fans, air-conditioners, lights, etc) automatically by using a mobile phone that connected to a simple microcontroller circuit. The process begins by sending a simple SMS to the recipient; the mobile phone that has been connected to the microcontroller circuit placed at the corner of your home or office. Receiver is a mobile phone (Nokia 3315) that can be used to send or receive SMS. If a user sends an SMS to find out the status of electrical equipment either ON or OFF, mobile phones will respond by telling that there is appliances that has not been closed and where it is installed. When the status is known, the user can do what they want, for example. If users want to switch the room lights ON, he only needs to send a SMS with the keyword 'ON' to the receiver, and immediately, the micro controller circuit will encode the keywords and send instructions to trigger the microcontroller circuit to switch on the light. The same thing also happens when users want to control other electrical equipment. This system can be used anywhere, as long as it in the range of phone network provide by the operators.